Wild forest elephants shake down fruit and leaves from trees - Fiona Maisels; Stephen Blake; Andrea Turkalo (Pachyderm)
This short paper reviews aspects of observed feeding behaviour of forest elephants in the vicinity Bomassa near of the headquarters of Nouabale-Ndoki NP, near the Dzanga Clearing and in Gamba. These observations suggest that 'forest elepants frequently manipulate both objects and inedible parts of food plants to obtain food as part of their behavioural repertoire'. The assumption that forest elephant simply eat the fallen fruit is no longer valid, these observations note animals knocking fruit down by throwing sticks, using branches to swipe at fruit and foliage, shake trees, and push at trunks in order to bring down fruit. Night observations in the vicinity Bomassa and assessment of the appearance of the ground around favoured food trees in other areas notes fruits from trees such as Pseudospondias microcarpa, Myrianthus aboreus and Tetrapleura tetraptera, Omphalocarpum elatum and Chrysophyllum lacourteanum are taken by either repeatedly shaking the trunks of the smaller trees or repeatedly pushing against the larger ones. Near the Dzanga Clearing elephants have been heard and observed knocking fruit from additional tree species. Pygmies claim that elephants wait for fruit of certain trees to ripen and fall rather than attempt to gain quick access to the fruits by knocking them down. A film crew in Gamba noted elephant knocking Borassus aethiopum fruits down.